A scientific data-driven comprehensive review on seven prevalent species under Acacia (Fabaceae): insights into phytochemical investigation and pharmacological potentials - Shreetama Roy; Amrita Ghosh; Milan Jana; Jyochhana Priya Mohanty; Nihar Ranjan Bhuyan (Journal of Applied Pharmaceutical Research, 2026)
Background: In traditional medicine, plants are important. For ages, various medicinal plants have been used for traditional medicine formulations, many of which are still in use today. There are many species under the genus Acacia that are important for medicine, most of which are found in Asia. Numerous species in the genus Acacia have long been used to treat a range of conditions, from mild ailments to serious cancers. Several species in this genus have been used in pharmaceutical and cosmeceutical formulations and have achieved commercial success due to their versatile medicinal properties. Methodology: The review followed the in-depth analysis of seven prevalent Acacia species. After screening an initial pool of approximately 500 articles on these species from sources such as PubMed and Scopus (2000–2026), around 120 publications were selected based on inclusion criteria (e.g., a focus on phytochemistry/pharmacology). This timeline highlights the novelty of the review while documenting emerging findings. Result and Discussion: Numerous studies in phytochemistry, pharmacology, and toxicology have demonstrated the positive therapeutic properties of substances such as betulin, catechin, diosgenin, kaempferol, and others for illnesses. In addition, numerous novel compounds with intriguing bioactivities have been disclosed by researchers. Conclusion: The species' pharmacological investigations and phytochemical analyses have been addressed and explained. In addition, botanical description and traditional applications are briefly discussed. The isolated compounds and their biological activities are discussed. All things considered, the genus Acacia emerges as a notable source of bioactive molecules with significant potential for pharmacognostical and drug development research in the years to come, especially in oncology.